PERAN PEMERINTAH PEKON DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK - Aulia Sari, Putri; Inti Suryani, Eny; Yonnawati, Yonnawati (Governance, 2025)
The role of village government is very important for the progress of a village. One of the functions of village government is to provide services while improving the quality of public services to the community in order to create a developed and prosperous society. As the government unit closest to the community, the pekon government functions as a liaison between the needs of the community and the policies taken by the government at a higher level. The aim of this research is to find out the role of the Pekon Government in improving the quality of public services in Pekon Teba Pering Jaya, Sukau District, West Lampung Regency in 2023. The research method used is qualitative with a descriptive approach with data collection using observation, interviews and documentation. Data analysis consists of reduction stages, data presentation, and drawing conclusions. The results of this research show that the Pekon government's role in efforts to improve the quality of services in Pekon Teba Pering Jaya is not yet optimal. This is due to the lack of facilities used in administrative services, so there is a need for proposals to procure facilities through village funds. There are Pekon officials who are not yet skilled in using electronic media or digital platforms, so socialization and training should be held to develop the human resources (HR) of Pekon Teba Pering Jaya officials.